Understanding Health Literacy Among Migrants in Portugal: The Impact of Environmental Issues - Rosa Machado; Madalena Garcia; Isaura Serra; Ana Lúcia João (Nursing Reports)
Background/Objectives: The health of migrant populations is strongly influenced by social, cultural, and environmental factors. Promoting health literacy (HL) is essential to empower these populations and reduce health inequalities. We aimed to assess the perceptions and behaviors of migrants residing in a neighborhood within a municipality in the Metropolitan Area of Lisbon regarding health risks arising from environmental conditions, as well as to determine their level of health literacy. Methods: Our cross-sectional, descriptive, exploratory study used the Health Literacy Questionnaire. This study was conducted with ethical approval including a sample of 101 participants. We performed descriptive and inferential statistical analyses using the Statistical Package for the Social Sciences (SPSS) version 29. Results: Most participants were from Portuguese-speaking countries and reported issues with indoor humidity and inadequate thermal comfort in both hot and cold conditions. The primary environmental issues identified included stagnant water, organic waste, and deficient electrical networks. Conclusions: The results revealed precarious housing conditions and inadequate support infrastructure, posing significant environmental health risks. Data revealed low levels of health literacy across most domains assessed.